Modelling and Process Control of Fuel Cell Systems - Hussain, Mohd Azlan; Wan Daud, Wan Ramli (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In this Special Issue, we have several papers related to fuel-cell-based cogeneration systems; the management and control of fuel cell systems; the analysis, simulation, and operation of different types of fuel cells; modelling and online experimental validation; and the environment assessment of cathode materials in lithium-ion battery energy generation systems. A paper which gives a comprehensive review with technical guidelines for the design and operation of fuel cells, especially in a cogeneration system setup, which can be an important source of references for the optimal design and operation of various types of fuel cells in cogeneration systems, can also be found in this Special Issue.